PERCOBAAN PENDAHULUAN PEMBUATAN SIRUP BERFRUKTOSA TINGGI DARIPATISAGU - Bambang Wiyono; Toga Silitonga; Eduard A S Sijabat (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
The purpose of this work is to study the effect of isomerization time and dosage of glucose isomeraseenzyme on the high fructose syrups (HFS) properties of sago starch. The basic raw material of HFS was glucose which made by the enzymatic acid hydrolysis process using hydrochloric acid and amiloglucosidase enzyme as catalyst. The isomerization time varied from 18, 24, and 30 hours. The amount of enzyme applied was consecutively 1.2, 1. 7, and 2.2 g/kg based on dry-weight of glucose syrups for each of the isomerization time.The result indicated that the isomerization time gave highly significant effect on the fructose content and on the degree of eonueresion of the fructose. The isomerization time also gave a significant effect on the dextrose equivalent. Increased isomerization time tends to give quadratic relationship with the dextrose equivalent, fructose content, and with the degree of conversion. Substituting and interpolating these quadratic equation, revealed that isomerization time of 24.66 to 25 hours, produced dextrose equivalent of 91.22 to 91.34, fructose content from 32.81 to 32.84 %, and degree of conversion of 36.17 to 36.34 %. These value are somewhat lower than the minimum acceptable HFS requirements which posses .the sweetness level as invert sugar, for dextrose equivalent, fructose content and degree of conversion of 96,42 %. and 50 %, respectively. Consequently, the HFS produced from sago starch rendered low sweetness level than that of the invert sugars.id